2022
DOI: 10.1097/md.0000000000025578
|View full text |Cite
|
Sign up to set email alerts
|

Management of adverse effects associated with pegylated Escherichia coli asparaginase on coagulation in the treatment of patients with NK/T-cell lymphoma

Abstract: Natural killer/T-cell lymphoma (NK/TL) is a chemotherapy-sensitive disease, and asparaginase-based chemotherapy has become the standard primary treatment for patients with this malignancy recently. The objective of this study was to evaluate the adverse reactions on blood coagulation of the administered pegylated Escherichia coli (E coli) asparaginase (PEG-ASP) to the NK/TL patients. Clinical data of 71 NK/TL patients (range 13-73 years), who received 239 cycles of chemotherapy treatment containing PEG-ASP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Its main feature is the secretion of IL-17A. In addition, differentiated and mature Th17 also secretes several cytokines such as IL-6, IL-21, IL-22, IL-23, and so on, which mediate the production of inflammatory diseases (18,42,43). Recently, it is reported that the concentration of Th17 cells and related cytokines (IL-17, IL-22 and IL-23) are significantly increased in some tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Its main feature is the secretion of IL-17A. In addition, differentiated and mature Th17 also secretes several cytokines such as IL-6, IL-21, IL-22, IL-23, and so on, which mediate the production of inflammatory diseases (18,42,43). Recently, it is reported that the concentration of Th17 cells and related cytokines (IL-17, IL-22 and IL-23) are significantly increased in some tumors.…”
Section: Discussionmentioning
confidence: 99%